2012
DOI: 10.3758/s13415-012-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological differences in reward processing in anhedonics

Abstract: Anhedonia is characterized by a reduced capacity to experience pleasure in response to rewarding stimuli and has been considered a possible candidate endophenotype in depression and schizophrenia. However, it is still not well understood whether these reward deficits are confined to anticipatory and/or to consummatory experiences of pleasure. In the present study, we recorded electrophysiological responses (event-related brain potentials [ERPs] and oscillatory activity) to monetary gains and losses in extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 84 publications
(133 reference statements)
10
46
0
Order By: Relevance
“…However, the effects of monetary gains in gambling tasks-which we replicate here-are very robust and have been widely studied both in EEG and fMRI (Camara et al, , 2010Ripollés et al, 2014;Carlson et al, 2011;Marco-Pallarés et al, 2008Sescousse et al, 2013;Cohen et al, 2007;Padrao et al, 2013). In addition, in the gambling task used in this study, the amounts of overall monetary gains and losses were fixed and equal for all participants and sessions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the effects of monetary gains in gambling tasks-which we replicate here-are very robust and have been widely studied both in EEG and fMRI (Camara et al, , 2010Ripollés et al, 2014;Carlson et al, 2011;Marco-Pallarés et al, 2008Sescousse et al, 2013;Cohen et al, 2007;Padrao et al, 2013). In addition, in the gambling task used in this study, the amounts of overall monetary gains and losses were fixed and equal for all participants and sessions.…”
Section: Discussionmentioning
confidence: 96%
“…Previous Electroencephalography (EEG) and Magnetoencephalography (MEG) human studies using time-frequency (TF) decomposition have revealed a mid-frontal BOA elicited by positive outcomes (20-30 Hz, peaking 200-400 ms after positive feedback; Cohen et al, 2007;Marco-Pallarés et al, 2008;Marco-Pallarés et al, 2009;Cunillera et al, 2012;HajiHosseini et al, 2012;Leicht et al, 2013;Luft et al, 2013;Padrao et al, 2013) and reward-predicting cues (Bunzeck et al, 2011;Kawasaki and Yamaguchi, 2013;Apitz and Bunzeck, 2014). This gain-related signal has been associated to the engagement of rewardrelated brain networks due to the fact that BOA shows a similar pattern in response to rewards than that observed in midbrain dopaminergic and striatal neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the PE group, the social anhedonia group did not differ from the control group in their behavioral performance or in their FRN for unexpected trials on the RLT, suggesting that some aspects of reward and punishment-based learning may to some extent be intact in people with extremely elevated social anhedonia who are at increased risk for schizophrenia-spectrum disorders (Karcher et al, 2015b;Padrao et al, 2013). Future research should continue to examine whether some particular aspect of reward and punishment-based learning, perhaps reward anticipation (Dowd and Barch, 2012;Juckel et al, 2006), is associated with anhedonia in at risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…In MDD, anhedonia and apathy are considered biological markers contributing to the overall picture of depression [26,27]. In schizophrenia, avolition is considered an endophenotype that contributes to the negative symptoms [15,28,29].…”
Section: Anhedonia Apathy and Avolition Versus Immobility And Diminmentioning
confidence: 99%